2007
DOI: 10.1158/0008-5472.can-06-4067
|View full text |Cite|
|
Sign up to set email alerts
|

Listeria monocytogenes Promotes Tumor Growth via Tumor Cell Toll-Like Receptor 2 Signaling

Abstract: The contribution of bacterial infection to tumorigenesis is usually ascribed to infection-associated inflammation. An alternate view is that direct interaction of bacteria with tumor cells promotes tumor progression. Here, we show that the microenvironment of large tumors favors bacterial survival, which in turn directly accelerates tumor growth by activating tumor cell Toll-like receptors (TLR). Listeria monocytogenes (Lm) survives in the microenvironment of large but not small tumors, resulting in the promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 32 publications
3
140
0
3
Order By: Relevance
“…We recently demonstrated that the level of TLR2 expressed on B16F10 melanoma cells determines their invasive activity in response to the endogenous factors released from tumor cells [12] . However, contradictory observations by others indicate that TLR2 activation is able to induce inflammatory cytokines and activate NK cells in vitro and in vivo and protect mice from tumor development and progression [31,32] . In the current study, we find that blocking TLR2 effectively reverses the immunosuppressive characteristics of the microenvironment by suppressing the expression of TGF-ÎČ1, IDO, and COX2 and attenuating the infiltration of M2 and Tregs cells.…”
Section: Discussionmentioning
confidence: 97%
“…We recently demonstrated that the level of TLR2 expressed on B16F10 melanoma cells determines their invasive activity in response to the endogenous factors released from tumor cells [12] . However, contradictory observations by others indicate that TLR2 activation is able to induce inflammatory cytokines and activate NK cells in vitro and in vivo and protect mice from tumor development and progression [31,32] . In the current study, we find that blocking TLR2 effectively reverses the immunosuppressive characteristics of the microenvironment by suppressing the expression of TGF-ÎČ1, IDO, and COX2 and attenuating the infiltration of M2 and Tregs cells.…”
Section: Discussionmentioning
confidence: 97%
“…Although proof-ofprinciple for this concept has been demonstrated with agonists of several TLRs (TLR3, -7, and -9) (8), only one, the TLR7 agonist Imiquimod, has been approved for clinical use [however, this is limited to topical treatment of basal cell carcinoma (9)]. The major clinical limitations of many TLR agonists are the risk of dose-limiting toxicities associated with their systemic delivery (10)(11)(12) and metastasis stimulation (13)(14)(15). Furthermore, some previously investigated TLR agonists are restricted to injection directly into tumor tissue (3,(16)(17)(18), an approach that will likely have limited therapeutic value in cancer patients with metastatic disease.…”
mentioning
confidence: 99%
“…T cells stimulated by MPs-treated DCs were used as effector cells and Lminfected or uninfected H22 liver tumor cells (BALB/c background) were used as target cells. 18 We found that the effector T cells lysed Lm-infected H22 cells but not uninfected H22 cells (Figure 4a). Therefore, MPs from Lm-infected macrophages contained Lm components, which might induce T cells to kill Lm-infected cells.…”
Section: Macrophages Participate In DC Presenting Lm Antigens In Vitromentioning
confidence: 88%
“…18 Briefly, H22 hepatocarcinoma tumor cells were infected by incubation with Lm (1 : 100 ratio) for 2 h, and then cultured with 100 mg/ml of gentamycin for 24 h. Tumor cells were labeled with CFSE and used as target cells. After incubation with MPs isolated from the supernatants of Lm-infected macrophages, bone marrow-derived DCs were cultured with T cells for 10 days.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%